Study of a treatment planning system efficiency to estimate the absorbed dose by pacemakers in external radiotherapy. (September 2016) - Gutiérrez, S.M.; Silva, S.; Dias, F.; Santos, J.A.M.; Lencart, J.
Abstract : Introduction: The number of patients with pacemakers receiving radiation therapy is increasing. It is well known that these devices are sensible to radiation and, according with the AAPM TG-34 guidelines, pacemakers should not be irradiated with primary radiation fields. Absorbed dose should be estimated before treatment and should not exceed 2 Gy. Purpose: The purpose of this work was to assess the accuracy of Varian Eclipse Treatment Planning System (TPS) used to estimate the absorbed dose by pacemakers. Material and methods: Two VMAT plans (faciocervical and oesophagus areas), previously used to treat patients with pacemakers, were simulated in a Rando phantom. Doses were computed on the Eclipse TPS. In both plans, the distance between the pacemakers and the border of the treatment fields was less than 15 cm. Gafchromic EBT3 films were used to measure dose. For each plan, a piece of film was placed between phantom slices at estimated pacemaker position. The plans were delivered in a Varian Trilogy linac. 2D calculated dose distributions were compared with the dose distributions of irradiated films using the software DoseLab. Calculated absorbed dose on the pacemaker was estimated by the dose-volume histogram (DVH). Results: Irradiated films showed higher doses in the pacemaker than the TPS prediction: 5% in the oesophagus and 13% in the faciocervical plan. In the former case, the pacemaker is closer to the field border (8 cm vs 10.2 cm, respectively). Conclusions: The TPS underestimates dose in the region where pacemakers are usually placed. Other methodologies should be implemented in the future to improve dose estimation. Disclosure: The authors have no relevant financial or non-financial relationships to disclose.